1980
DOI: 10.1515/znb-1980-1125
|View full text |Cite
|
Sign up to set email alerts
|

1,2-Dimethoxy-4-isopropoxy-5-vinylbenzene, an Insect anti-Juvenile Hormone Lacking the Chromene Ring

Abstract: AbstractThe chromene derivative precocene II (1) induces precocious metamorphosis and sterility on some insects, while β-asarone (2), which does not contain a chromene ring, reveales sterilant action without causing developmental disturbances. Based on the common structural features of these two substances, some of their analogues containing their structural elements have been prepared and tested on the cotton bug, Dysdercus cingulatus to investigate structural requirements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The alkoxyvinylbenzene derivatives 4-8were more toxic. The vinylbenzenes with three alkoxy groups (7)(8) were less toxic than those with two (4-6). At 0.05% the toxicity of4-6 was lost.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The alkoxyvinylbenzene derivatives 4-8were more toxic. The vinylbenzenes with three alkoxy groups (7)(8) were less toxic than those with two (4-6). At 0.05% the toxicity of4-6 was lost.…”
Section: Resultsmentioning
confidence: 90%
“…This compound caused both precocious metamorphosis and a de- [OJ 20 crease in egg production by D. cingulatus. In this paper we describe the synthesis and the sterilizing and toxic activities of other 5isopropoxy-4-vinylbenzenes (4)(5)(6)(7)(8) and of alkoxybenzenes without double bond. Scale insects, which are seldom used in insect antihormonestudies, were the test organisms.…”
Section: Coumpound7 Is a Precocene Derivative Withmentioning
confidence: 99%
“…8 ) Compounds 4! "'V8 did not affect the morphology of P. cirri, but their toxic and sterilizing activities surpasses those of precocenes.…”
Section: "'26)mentioning
confidence: 99%
“…Brooks et al, 1979). Matolcsy et al (1980) have also reported AJH activity against the cotton bug, Dysdercus, for a precocene analogue that lacks the chromene ring.…”
mentioning
confidence: 94%